2021
DOI: 10.1038/s41467-021-22701-3
|View full text |Cite
|
Sign up to set email alerts
|

Local field potentials in the parietal reach region reveal mechanisms of bimanual coordination

Abstract: Primates use their arms in complex ways that frequently require coordination between the two arms. Yet the planning of bimanual movements has not been well-studied. We recorded spikes and local field potentials (LFP) from the parietal reach region (PRR) in both hemispheres simultaneously while monkeys planned and executed unimanual and bimanual reaches. From analyses of interhemispheric LFP-LFP and spike-LFP coherence, we found that task-specific information is shared across hemispheres in a frequency-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…1. Details of the electrophysiological data are provided in previously published studies [43][44][45][46] . Animals reached with the left (unimanual), right (unimanual), or both hands together (bimanual-together) to a single target or moved each hand to a different target (bimanual-apart) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Details of the electrophysiological data are provided in previously published studies [43][44][45][46] . Animals reached with the left (unimanual), right (unimanual), or both hands together (bimanual-together) to a single target or moved each hand to a different target (bimanual-apart) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b). We focused on the high beta band (15-40 Hz), which has been implicated in motor planning 42, 43 . Our results suggest that PRR determines the spatial goal of coordinated eye and arm movements and that PRR and LIP operate in parallel to process arm and eye movements, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These effects were observed in the high-beta range (above 20Hz), and not in the lower beta range (15-20Hz). The specific role of subbands in the beta range remains poorly understood, but a small number of studies point towards a particular relevance of high-beta for integration of motor signals (Mooshagian, Holmes, and Snyder 2021;Tia et al 2017), with the high-beta range selectively altered during the observation of other people's actions (Simon and Mukamel 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is mounting evidence that the signaling of feedback predictions, and feedforward prediction errors, respectively, are associated with directed information transfer in distinguishable frequency bands, namely the beta and gamma band, respectively (Andre M. Bastos et al, 2015;Bastos et al, 2012;Fries, 2015). Between the premotor and parietal lobes, the high-beta (20-30Hz) and gamma (60-90Hz) frequency bands seem particularly involved in the integration of information (Mooshagian et al, 2021;Tia et al, 2017). If we use the stimuli from our fMRI studies (Table 1), in which participants viewed the same acts in either predictable (intact) sequences or in unpredictable (temporally scrambled) sequences, matched for low-level features using camera changes for both sequences (Figure 1 and Supplementary Figure S1), the predictive coding account makes two testable predictions: the supramarginal gyrus (SMG) should receive more precentral (PreCG) feedback in the high-beta range for intact sequences, and more feedforward prediction errors from the middle occipital gyrus (MOG) for the scrambled sequences (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Bimanual coordinated tasks seem critical for detecting consistent hand preferences in NHP (Hopkins et al, 2003b;Schweitzer et al, 2007;Zhao et al, 2010) due to the cognitive and neural demands of these tasks. In contrast to unimanual actions, bimanual tasks require interhemispheric information transfer (Mooshagian et al, 2021) and a more complex coordination of both hands that relies on extensive cortical and subcortical neural networks (Donchin et al, 1998;Puttemans et al, 2005;Swinnen, 2002), including the cerebellum (van Dun et al, 2021). Specifically, some studies with NHP have revealed that manual preferences are correlated to neuroanatomical asymmetries within the primary motor cortex during the bimanual tube task (Hopkins and Cantalupo, 2004;Phillips and Sherwood, 2005), but also in complex unimanual task requiring skilled finger manipulation (Nudo et al, 1992).…”
Section: Heterogeneity In the Use Of Different Bimanual Tasksmentioning
confidence: 99%